Inference of economic truth from financial statements for detecting earnings management: inventory costing methods from an information economics perspective. (27th December 2017) - Herath, Hemantha S.B.; Lu, Xiaoting
Abstract : We introduce uncertainty in the classic inventory costing choice problem to investigate the underlying partitions imposed by two accounting inquiries (processes of generating information): variable costing and absorption costing. In a contemporaneous reporting environment, we show that absorption costing provides a finer partition of the state space compared to variable costing when a firm arbitrarily increases the production level (opportunistic overproduction), and the predetermined fixed overhead rate is adjusted. Grounded in an information economics perspective, the intent of the article is to propose an approach to detect real earnings management by extracting information from financial statements. The resulting managerial biases arising from earnings management are also discussed.